Antiinflammatory Activity from Marine Microalgae Chlorella vulgaris Extract Used Human Red Blood Cells Stability Method (HRBC) - Dewi kurnia; Nadya Prisdayanti; Lia Marliani; Idar Idar; Zeily Nurochman (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
The biologic protection response against disruption in the body can be an inflammatory reaction. Medications commonly used to treat inflammation are steroids and non-steroids which, if used over a long period, can cause adverse side effects. Several studies have shown that microalgae can be used as an anti-inflammatory agent. This research was conducted to determine the anti-inflammatory activity of the Chlorella vulgaris microalgae extract. Extraction was carried out by multilevel maceration method using n-hexane, chloroform, and ethanol. TLC monitoring results showed that the Chlorella vulgaris extract contained flavonoid, phenol, alkaloid, and steroid saponin compounds. The anti-inflammatory activity test of the extract was carried out used Human Red Blood Cell (HRBC) stability method with Na-diclophenac as a comparison standard. The results showed the inhibition value of red blood cell hemolysis (IC50) in n-hexane, chloroform and ethanol extracts respectively 150,399; 83.852 and 92.349% with the inhibition value of Na-diclophenac standard of 55.149%. Chloroform extract is known to have the most active anti-inflammatory activity which is 83,852 ppm. The results of this study indicate that the chloroform extract in Chlorella vulgaris microalgae has the potential as an anti-inflammatory agent that can be developed as an alternative anti-inflammatory drug from natural marine materials. Keywords: anti-inflammatory, Chlorella vurlgaris, Human Red Blood Cells (HRBC)